TmSR-C, scavenger receptor class C, plays a pivotal role in antifungal and antibacterial immunity in the coleopteran insect Tenebrio molitor. (October 2017) - Kim, Soo Gon; Jo, Yong Hun; Seong, Jeong Hwan; Park, Ki Beom; Noh, Mi Young; Cho, Jun Ho; Ko, Hye Jin; Kim, Chang Eun; Tindwa, Hamisi; Patnaik, Bharat Bhusan; Bang, In Seok; Lee, Yong Seok; et al.
Abstract : Scavenger receptors (SRs) constitute a family of membrane-bound receptors that bind to multiple ligands. The SR family of proteins is involved in removing cellular debris, oxidized low-density lipoproteins, and pathogens. Specifically, class C scavenger receptors (SR-C) have also been reported to be involved in phagocytosis of gram-positive and -negative bacteria in Drosophila and viruses in shrimp. However, reports are unavailable regarding the role of SR-C in antifungal immune mechanisms in insects. In this study, a full-length Tenebrio molitor SR-C ( Tm SR-C) sequence was obtained by 5′- and 3′-Rapid amplification of cDNA ends-polymerase chain reaction (RACE-PCR). The TmSR-C full-length cDNA comprised 1671 bp with 5′- and 3′-untranslated regions of 23- and 107-bp, respectively. Tm SR-C encodes a putative protein of 556 amino acid residues that is constitutively expressed in all tissues of late instar larvae and 2-day-old adults, with the highest transcript levels observed in hemocytes of larvae and adults. TmSR-C mRNA showed a 2.5-fold and 3-fold increase at 24 and 6 h after infection with Candida albicans and β-glucan, respectively. Immunoassay with Tm SR-C polyclonal antibody showed induction of the putative protein in the cytosols of hemocytes at 3 h after inoculation of C. albicans . RNA interference (RNAi)-based gene silencing and phagocytosis assays were used to understand the role of Tm SR-C in antifungal immunity. Silencing of TmSR-C transcripts reduced the survivability of late instar larvae at 2 days post-inoculation of C. albicans, Escherichia coli, or Staphylococcus aureus . Furthermore, in TmSR-C -silenced larvae, there was a decline in the rate of microorganism phagocytosis. Taken together, results of this study suggest that Tm SR-C plays a pivotal role in phagocytosing not only fungi but also gram-negative and -positive bacteria in T. molitor . Graphical abstract: Highlights: A class C scavenger receptor (SR-C) gene was identified from the coleopteran insect, T. molitor, named as TmSR-C. Tm SR-C influenced on larval survivability against microbes. Tm SR-C plays a pivotal role in phagocytosis against fungi, and Gram-negative and -positive bacteria in T. molitor .